SARS-CoV-2 and co-infections detection in nasopharyngeal throat swabs of COVID-19 patients by metagenomics (2020)
e read with interest a recent article in this journal regarding co-infections in people with COVID-19.1 Rapid and simultaneous detection of SARS-CoV-2, the cause of COVID-19, and co-infections is essential for clinical management of COVID-19 patients. However, the diversity of possible co-infecting pathogens (bacteria and viruses) challenges conventional diagnostics approaches (bacterial culture and PCR). Metagenomics is a sensitive pan-pathogen assay for infectious disease diagnosis and the discovery of novel pathogens.2 However, there have been only three studies reporting the application of metagenomics to detect SARS-CoV-2 and coinfections, with a combined sample size of nine patients.3–5 Since the beginning of March 2020 an observational study have been conducted at the Hospital for Tropical Diseases (HTD) in Ho Chi Minh City, Vietnam and another one at one of its two designated centers for receiving and treating COVI-19 patients from southern Vietnam with a population of over 40 million (Supplementary Figure 1). We enrolled patients with a confirmed SARSCoV-2 diagnosis by a WHO recommended assay admitted to the study settings within 48 h. We collected nasopharyngeal throat swabs (NTS), clinical and laboratory data, and travel and contact history from each study participant. The collected NTS was stored at 4 °C at the study sites within four hours and was then transferred to the clinical laboratory of HTD for analysis. The clinical studies received approvals from the Institutional Review Board of the HTD and the Oxford Tropical Research Ethics Committee of the University of Oxford. Study participants gave their written informed consent.